2018
DOI: 10.1111/mms.12517
|View full text |Cite
|
Sign up to set email alerts
|

Response to capture stress involves multiple corticosteroids and is associated with serum thyroid hormone concentrations in Guadalupe fur seals (Arctocephalus philippii townsendi)

Abstract: Guadalupe fur seals are a threatened species with few breeding locations, which potentially makes them sensitive to environmental or anthropogenic stressors. We present the first study to quantify adrenal and thyroid function in this species in an effort to measure their stress response to capture. We analyzed a suite of corticosteroid hormones released over time during capture in both adult females (n = 10) and weanling pups (n = 26) during March 2016. Multiple corticosteroids were released during capture, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 74 publications
(140 reference statements)
2
14
0
1
Order By: Relevance
“…Interestingly, 40% of California sea lions and northern fur seals and 27% of Steller sea lions had F:B ratio < 1.0. The variability in the GC ratios we found were not completely surprising as a recent study found the F:B ratios in serum ranged between 6.5 and 16.2 in Guadalupe fur seals during an acute stress response ( DeRango et al , 2018 ). We also found cortisol and corticosterone were correlated, explaining between 58 and 63% of the variability in the three otariid species.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Interestingly, 40% of California sea lions and northern fur seals and 27% of Steller sea lions had F:B ratio < 1.0. The variability in the GC ratios we found were not completely surprising as a recent study found the F:B ratios in serum ranged between 6.5 and 16.2 in Guadalupe fur seals during an acute stress response ( DeRango et al , 2018 ). We also found cortisol and corticosterone were correlated, explaining between 58 and 63% of the variability in the three otariid species.…”
Section: Discussionsupporting
confidence: 56%
“…Assessing the impact of potential stressors in pinnipeds is logistically challenging and often requires capture and handling ( DeRango et al , 2018 , Keogh et al , 2013 ). Many stress-related hormones can be altered during this process, thus limiting the utility of metabolically active tissues, such as blood ( Atkinson et al , 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional research on a larger number of whales of differing sex and age-class is needed to determine the relative responsiveness of both GCs to different types of both natural (e.g., pregnancy, lactation) and anthropogenic stressors, to develop a reference dataset of baleen GC levels, and to better understand the biological relevance and temporal aspects of increased baleen hormone concentrations. Recent research on both terrestrial and marine species has suggested that the two GCs may signal independently, and, therefore, studies of acute and chronic stress should include analysis of both hormones (Koren et al 2012, Chinn et al 2018, DeRango et al 2019.…”
mentioning
confidence: 99%